“It’s Not Good to Be Sick and Have the Child”: Perspectives on Pregnancy After HIV-Positive Diagnosis Among Women in Western Jamaica - Andrews C; Reuter TK; Londono V; Claye L; Aung M; Jolly P (International Journal of Women's Health, 2022)
Courtney Andrews,1 Tina Kempin Reuter,1 Valeria Londono,2 Lea Claye,3 Maung Aung,4 Pauline Jolly3 1Institute for Human Rights, University of Alabama at Birmingham, Birmingham, Alabama, USA, Birmingham, AL, USA; 2Minority Health Research Training, University of Alabama at Birmingham, Birmingham, AL, USA; 3Department of Epidemiology, University of Alabama at Birmingham, Birmingham, AL, USA; 4Epidemiology and Research Unit, Western Regional Health Authority, Ministry of Health, Montego Bay, JamaicaCorrespondence: Courtney Andrews, Institute for Human Rights, University of Alabama at Birmingham, HHB 551, 1720 2 nd Avenue South, Birmingham, AL, 35294-1152, USA, Tel +1 205 975 6492, Email cjandrews@uab.eduPurpose: To identify factors associated with reproductive decision-making for women living with HIV in Western Jamaica, to assess their confidence in anti-retroviral therapy to reduce the chances of mother to child transmission of HIV, and to better understand the experience of stigmatization surrounding becoming pregnant after HIV diagnosis.Participants and Methods: Two focus groups were conducted among women living with HIV in the four parishes of Western Jamaica in 2011. A trained moderator conducted the focus groups along with two student notetakers. Qualitative coding and content analysis were used to identify common themes and exemplary quotations characterizing those themes.Results: Participants agree that adherence to antiretroviral therapy as prescribed by a physician facilitates better health and longevity; however, they were conflicted on the efficacy of the therapy to prevent mother to child transmission of the virus. Participants report that becoming pregnant after HIV diagnosis continues to be highly stigmatized. Among participants, fear of MTCT and concern that their children will be mistreated are the primary drivers of reproductive decision-making.Conclusion: Despite advances in HIV treatment and assisted technologies to prevent MTCT, participants show skepticism that ARV medication is effective at preventing MTCT. Stigma and discriminatory behavior by community members and health-care professionals continue to shape reproductive decision-making for the women who participated in this study. More informed counseling that includes education on recent advancements in HIV treatment and its efficacy at preventing MTCT should be more widely available to pregnant women. To reduce stigma and discriminatory behavior, this education should extend to the larger community.Keywords: HIV, reproduction, mother to child transmission, stigma